MiR-196a: is it the 'silver bullet' against Huntington's disease?. (January 2014) - Saba, Reuben; Booth, Stephanie A
EVALUATION OF:  Cheng PH, Li CL, Chang YF et al. miR-196a ameliorates phenotypes of Huntington diseases in cell, transgenic mouse, and induced pluripotent stem cell models. Am. J. Hum. Genet. 93(2), 306–312 (2013). This study reports on the therapeutic potential of miR-196a in alleviating the molecular, pathological and behavioral deficits associated with Huntington's disease in several model systems, often used in the study of the disease. miR-196a appears to confer a robust neuroprotective role through the targeting of molecules that are downstream of the neurodegenerative cascade and part of the ubiquitin proteosome, gliosis and CREB pathways. miR-196a, however, does not appear to target HTT or mutHTT. Owing to the far-reaching role of the miRNA, it may be considered relevant in the treatment options of other brain diseases and disorders characterized by the misfolding and aggregation of host proteins of the CNS.